THE IMPORTANCE OF CULTURE IN TEACHING ENGLISH AS FOREIGN LANGUAGE FOR TEACHERS IN BULELENG - GEDE AGUS JUNIARTHA (JETA (Journal of English Teaching and Applied Linguistic), 2024)
The objective of this study is to determine the significance of culture in the teaching of English as a second language for teachers in Indonesia specifically in Buleleng regency. This study employs a blend of qualitative methodologies and library research. Specifically, one teacher from SD N 1 Kaliuntu serves as an informant to provide answers for the inquiry conducted in this research. The findings indicate that culture plays a crucial role in the instruction of English as a foreign language, as it can inspire students by demonstrating how the language is utilized in their home country. Teachers, as facilitators in education, are also responsible for incorporating culture into every instructional process. This ensures that students learn in alignment with the prevailing reality.